The Role of Auditing in Detecting Practices of earnings Management and Reporting at Iraqi Stock Exchange - Salwan Oujah; Muhammad Reza Abbaszadeh (مجلة الغري للعلوم الاقتصادية والادارية)
Previous studies in the field of profit management prove two main approaches for such a management. CEOsare able to manage benefits through accruals as well as actual activities manipulation (Hilly et al., 1999). Profit management literature mostly insist on profit management based on accruals. However, quantitative studies regarding actual profit management had been carried out. Actual profit management is accompanied by change in timing or the structure of actual activities. 310 Therefore, the researchers of actual profit management look for detecting abnormal levels of entity’s activities (Legni et al., 2009). CEOs take advantage of two management methods based on accruals and real profit management to manipulate benefit. In the first approach, management is done through manipulating accruals to accounting numbers in accordance with its required goals. In this method, the CEO manages the profit through accelerating income recognition as well as delay in recognition of expenses to present a better performance in the current period. However, the CEO turns to the actual profit management through adopting some operational decisions, i.e. manipulating real activities, reaches the required benefit. Studies such as Hilly and Wellen (1999), Fadenburgh and Tiroul (1995), Dichou and Skinner (2000) and Roichodury (2006) point to approaches such as sales through discount, changes in shipping table, reduction in discretionary spending, for instance expenses of research and development, as well as overproduction as management methods.